Legionella pneumophila effector WipA, a bacterial PPP protein phosphatase with PTP activity - Jia, Qian; Lin, Yun; Gou, Xuejing; He, Lei; Shen, Dong; Chen, Dongni; Xie, Wei; Lu, Yongjun (Acta biochimica et biophysica Sinica, 2018)
Abstract The gram-negative bacterium Legionella pneumophila invades human’s lung and causes Legionnaires’ disease. To benefit its survival and replication in cellular milieu, L. pneumophila secrets at least 330 effector proteins into host cells. We found that the effector WipA has the protein tyrosine phosphatase (PTP) activity but does not depend on the classical CX5R motif for activity, suggesting that WipA is an unconventional PTP. Meanwhile, the presence of three other highly conserved motifs typically seen in protein serine/threonine phosphatases and the poor inhibition of WipA activity by okadaic acid led us to propose that WipA is a bacterial protein phosphatase. In addition, the determination of the 2.55-Å crystal structure of WipA revealed that WipA resembles cold-active protein tyrosine phosphatase (CAPTPase), and therefore very likely shares the same catalytic mechanism.